Outcome of Laparoscopic Cholecystectomy as a Day Case Procedure - Rabia Ramzan, Danish Afzal, Abeera Ishaq Butt, Muhammad Hassaan, Muhammad Zeeshan Sarwar, Syed Asghar Naqi, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Gallstone disease, a condition caused by the development of stones in gall bladder, usually presents with pain in upper abdomen, is one of the most common diseases of digestive system. It can be treated by the surgical removal of gall bladder, either through open cholecystectomy or by laparoscopic cholecystectomy (key hole surgery); the latter allows patients to be discharged from hospital on the day of their surgery, a concept known as day case surgery. Material and Methods: It was a descriptive case series in which 100 patients were selected through non probability, consecutive sampling. Inclusion and exclusion criteria were applied. Patients were assessed by anesthetist and consultant surgeon before undergoing laparoscopic cholecystectomy. After surgery, patients were encouraged intake of liquids and were discharged from the hospital as soon as they fulfilled the discharge criteria. Unplanned overnight admissions determined the outcome of this study. Results: 86% patients were discharged on the same day of surgery and 14% patients had an overnight stay after surgery. There were no readmissions but 3% of the patients presented for an unexpected consultation. Post stratification values of overnight admissions with age and BMI were found to be statistically significant while those for gender and duration of symptoms were found to be statistically insignificant. Conclusion: Patient selection is an important factor that affects the outcome of laparoscopic cholecystectomy, which is mostly an effective procedure. This study will help in the adoption of laparoscopic cholecystectomy as a day case procedure which is an effective way of reducing burden on health care resources. Keywords: Cholecystectomy, day case laparoscopic cholecystectomy (DCLC), laparoscopic surgery (LC).